2020
DOI: 10.1016/j.healthpol.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of price transparency on consumers and providers: A scoping review

Abstract: Escalating levels of healthcare spending and price variation in the healthcare market have driven government and insurer interest in price transparency tools that are intended to help consumers shop for services and reduce overall healthcare spending. However, it is unclear whether the objectives of price transparency are being achieved. We conducted a scoping review to synthesize the impact of price transparency on consumer, provider, and purchaser behaviours and outcomes.Price transparency tools had weak imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 32 publications
0
49
0
1
Order By: Relevance
“…Perhaps they preferred more health care services within the delivery episode. Previous research has generally shown that price transparency tools are not associated with selection of lower-priced facilities 7 , 8 , 9 , 10 , 11 ; more studies are needed to trace whether this finding would continue to be true over time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Perhaps they preferred more health care services within the delivery episode. Previous research has generally shown that price transparency tools are not associated with selection of lower-priced facilities 7 , 8 , 9 , 10 , 11 ; more studies are needed to trace whether this finding would continue to be true over time.…”
Section: Discussionmentioning
confidence: 95%
“… 3 , 4 , 5 , 6 Studies showed that use of these tools was associated with lower spending on imaging services but not on other services. 4 , 7 , 8 , 9 , 10 , 11 Nonetheless, price estimates for some medical services were queried more frequently than others. These so-called shoppable services tended to be routine, have higher out-of-pocket costs, and be nonemergent (eg, imaging services), allowing patients time to seek price information as they planned for care.…”
Section: Introductionmentioning
confidence: 99%
“…Insurance carriers could also make cost estimator tools available to patients online. These tools already exist for some insurance plans, but they have had very poor uptake, 40 , 42 , 43 , 44 perhaps in part because patients who use them still have to contact their clinicians to request alternative medications or procedures when costs are too high. Better yet, insurance companies could simplify their cost-sharing mechanisms, especially as evidence grows that patients are bad at choosing insurance plans that provide the most coverage for the least amount of money.…”
Section: Discussionmentioning
confidence: 99%
“…También existen interacciones entre precio y garantía, se debe considerar ambos factores simultáneamente cuando se elabora la estrategia de marketing, que determine ganancias y supervivencia. Además, el precio y la garantía deben ser igualmente importantes cuando realizan e integran las estrategias (Zhang, et al, 2020;Díaz & Díaz, 2018). En definitiva, dada la gran influencia que el precio tiene sobre la demanda y las ganancias, las políticas de precios son decisiones comerciales fundamentales, por los múltiples productos en diferentes categorías (Karray, Martín-Herrán, & Zaccour, 2020).…”
Section: • Preciounclassified